Samotność z perspektywy nieśmiertelności.Refleksje Henryka Elzenberga - Konstańczak, Stefan (Filozofia Chrześcijańska, 2015)
The starting point for the considerations are three versions of the text of Henryk Elzenberg, kept in manuscripts, and not published until now, devoted to “meditations” over the possibility of reaching immortality in earthly life. The author, on the basis of their analysis and other statements on immortality, presents Elzenberg’s attitude towards solitude, to which people who do not follow the main social stream and are able to retain autonomy of their views independently of outer conditions are all doomed. To indicate such kind of people Elzenberg has introduced the category of “spirit aristocracy”. This category is indispensable for existing of every society. And both scientists and artists are classified to it. They reach immortality, but it is conditioned, because during their lives nobody will get to know if it is worth to make a sacrifice of their own solitude. According to the author, Elzenberg’s life may be set as an example of such a solitary spirit aristocracy.